1993
DOI: 10.1007/bf01967444
|View full text |Cite
|
Sign up to set email alerts
|

Detection of toxigenicClostridium difficile in fecal samples by colony blot hybridization

Abstract: A hybridization assay for detection of toxigenic Clostridium difficile in fecal samples was developed and compared with the classical tissue culture cytotoxicity assay. A DNA fragment probe specific for the toxin B gene of Clostridium difficile was synthesized by the polymerase chain reaction and labelled with digoxigenin. Fecal samples were cultured for 24 hours, replica-plated and hybridized with the probe. The hybridization assay had a sensitivity of 100%, specificity of 96.7%, positive predictive value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Toxin production can be demonstrated by putting broth culture filtrates through the same EIAs used for faecal specimens, and also by the cell cytotoxicity assay. 105 Alternative methods reported include reversed passive latex agglutination (applied to toxin A), 106 colony blot probe-hybridisation (applied to toxin B), 107 and PCR (toxins A and B). 108 These so-called 'second-look' cytotoxicity assays can be shown to detect toxigenic C. difficile in diarrhoeal specimens negative in the stool cytotoxicity assay, but the clinical significance of this finding requires confirmation.…”
Section: Non-microbiological Methodsmentioning
confidence: 99%
“…Toxin production can be demonstrated by putting broth culture filtrates through the same EIAs used for faecal specimens, and also by the cell cytotoxicity assay. 105 Alternative methods reported include reversed passive latex agglutination (applied to toxin A), 106 colony blot probe-hybridisation (applied to toxin B), 107 and PCR (toxins A and B). 108 These so-called 'second-look' cytotoxicity assays can be shown to detect toxigenic C. difficile in diarrhoeal specimens negative in the stool cytotoxicity assay, but the clinical significance of this finding requires confirmation.…”
Section: Non-microbiological Methodsmentioning
confidence: 99%
“…We and several others have found that the presence of the genes encoding for toxin A and toxin B correlates with the presence of toxins, with very few exceptions (10,17,22,(31)(32)(33)(34). Two methods for the direct identification of the genes encoding for toxins have been described: colony blot hybridization, which is performed on replica primary plates inoculated with stool samples (29), and the detection of toxigenic C. difficile in stool samples by the PCR (15,18). Both methods have drawbacks.…”
mentioning
confidence: 99%